SCREENING OF HERBAL MOLECULES FOR THE MANAGEMENT OF ALZHEIMER’S DISORDER: In silico AND in vitro APPROACHES (Applied Biological Research, 2023)
The current therapeutics for Alzheimer’s disorder (AD) is aimed at  providing the symptomatic relief from AD and it continues to progress  steadily despite ongoing therapy. The present study was aimed to identify  the herbal molecules that could utilize multiple pathways of AD  pathogenesis for better AD management. One hundred herbal molecules  were selected and subjected to docking analysis against  acetylcholinesterase (AChE) (1EVE), butyrylcholinesterase (BChE) 4B0P), and Tau protein kinase (1J1B). Based on the docking score, RMSD  value, inhibition constant (Ki), and amino acids involved, β-carotene,  dihydrotanshinone-I, glabridin, liriodenine, morin, N-formylanonaine,  quercetin, quercitrin, rutin, sumaflavone, and vitisinol C were found to be  the best molecules. These molecules were then subjected to in vitro screening for their antioxidant and anti-inflammatory potential. Quercetin  and rutin were observed to be the most promising antioxidant and anti inflammatory molecules which could be beneficial during AD by targeting  the oxidative- and inflammatory-stress pathways. The results predicted  that quercetin has potential to target multiple pathways of AD  pathogenesis so could prove beneficial in treating AD; however, further  analysis is still required.
Keywords: Alzheimer’s disease; anti-inflammatory; antioxidant; molecular docking; quercetin; rutin